The role of natural biopolymers in genotoxicity of mutagens/carcinogens elimination - Miadoková, Eva; Svidová, Soňa; Vlčková, Viera; Dúhová, Viola; Pražmáriová, Eva; Tóthová, Katarína; Naďová, Slavomíra; Kogan, Grigorij; Rauko, Peter (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2005)
Nowadays naturally occurring compounds with the potential antimutagenic and anticarcinogenic effects are of great importance for their prospective use in cancer chemoprevention and treatment. The new water soluble derivative of microbial polysaccharide beta-D-glucan-carboxymethyl glucan (CMG) belongs to such a category of natural substances. CMG isolated from the cell wall of baker's yeast Saccharomyces cerevisiae is included into the class of biopolymers known as biological response modifiers (BRMs) with a broad range of activities, above all ones interfering with cancer therapy. It was demonstrated on four experimental model systems that biological and consequential medicinal importance of CMG is based on the combined application with another active compound. In the Saccharomyces cerevisiae antimutagenicity assay CMG significantly reduced ofloxacin-induced mutagenicity in the yeast strain D7. CMG exerted bioprotective (anti-toxic and antimutagenic) effect after its simultaneos application with methyl methanesulphonate on the repair-deficient strain uvs10 of the unicellular green alga Chlamydomonas reinhardtii. In the Vicia sativa simultaneous phytotoxicity and anticlastogenicity assay CMG exerted statistically significant anticlastogenic efect against maleic hydrazide-induced clastogenicity in Vicia sativa L. Only in the Salmonella/microsome assay CMG did not exert statistically significant antigenotoxic effect, despite of the fact that it reduced 9-aminoacridine-induced mutagenicity in S. typhimurium TA97, but his(+) revertants decreasing was statistically significant only at the highest CMG concentration used. The data presented unambiguously documented that even biopolysaccharides (e.g., derivatives of beta-glucan) belonging to the most abundant class of natural biopolymers may contribute to cancer prevention and therapy.
Keywords: testy genotoxicity; Anticarcinogenic Agents; antimutagenní látky; Mutagenicity Tests; Carcinogenicity Tests; beta-Glucans; testy karcinogenity; beta-glukany; Antimutagenic Agents; antikarcinogenní látky